Claudin-9 (CLDN9) promotes gastric cancer progression by enhancing the glycolysis pathway and facilitating PD-L1 lactylation to suppress CD8+ T cell anti-tumor immunity - Hu, Xingbin; Ouyang, Wenhao; Chen, Haizhu; Liu, Zhihong; Lai, Zijia; Yao, Herui (Cancer pathogenesis and therapy, 2025)
Gastric cancer (GC) is a common malignancy characterized by the absence of reliable prognostic indicators and effective therapeutic targets. Claudin-9 (CLDN9) has been demonstrated to be upregulated in various cancers. However, its prognostic value, biological function, and regulatory mechanisms in GC remain unclear. Therefore, this study aimed to elucidate the role of CLDN9 in GC progression and its underlying mechanisms. We utilized consensus cluster, random survival forest, and multivariate Cox regression analyses to identify CLDN9 in GC. Subsequently, we evaluated the mRNA and protein levels of CLDN9 in GC using quantitative real-time polymerase chain reaction (PCR) (qRT-PCR), Western blotting (WB), and immunohistochemistry (IHC). Furthermore, the role of CLDN9 in GC progression was investigated using a series of functional in vivo and in vitro experiments. Finally, we elucidated the molecular mechanisms of CLDN9 using bioinformatics, molecular biology, animal models, and patient tissue specimens. Two GC subtypes with survival and functional differences were identified based on glycolytic metabolic genes in the Cancer Genome Atlas (TCGA)- Stomach adenocarcinoma (STAD) dataset. A prognostic risk score was calculated using seven genes to assess the overall survival (OS) in GC. Using random survival forest and multivariate Cox analyses, we identified CLDN9 as the key gene linked to the glycolytic subtype and prognosis of GC. CLDN9 expression was significantly upregulated in patients with GC as well as in GC cells. CLDN9 knockdown inhibited tumor proliferation, invasion, and metastasis both in vivo and in vitro. Mechanistically, CLDN9 was found to regulate lactate dehydrogenase A (LDHA) expression and promote glycolytic metabolism by activating the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/hypoxia-inducible factor 1-alpha (HIF1α) signaling pathway. Additionally, lactate, a glycolytic metabolite, enhanced programmed cell death ligand 1 (PD-L1) lactylation and stability, which suppressed anti-tumor immunity in CD8+ T cells, thereby contributing to GC progression. CLDN9 expression is associated with GC development and progression. Mechanistically, CLDN9 enhances the glycolysis pathway and facilitates PD-L1 lactylation through the PI3K/AKT/HIF1α signaling pathway, thereby suppressing anti-tumor immunity in CD8+ T cells. CLDN9 has the potential to serve as a novel prognostic marker and therapeutic target for GC. [Display omitted] •Distinct glycolysis-related molecular subtypes in gastric cancer (GC) were identified using the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets.•The role of a key glycolysis-related gene in GC, Claudin-9 (CLDN9), was identified and characterized.•CLDN9 drives GC progression by regulating glycolytic metabolism through the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/hypoxia-inducible factor 1-alpha (HIF1α) signaling pathway.•CLDN9 affects programmed cell death ligand 1 (PD-L1) lactylation and modulates the anti-tumor immune response of CD8+ T cells.